The barbarian Sophist: Clement of Alexandria’s Stromateis and the Second Sophistic - Thomson, S (2014)
Clement of Alexandria, active in the second half of the second century AD, is one of the first Christian authors to explain and defend the nascent religion in the terms of Greek philosophy and in relation to Greek paideia. His major work, the Stromateis, is a lengthy commentary on the true gnosis of the Christian faith, with no apparent overarching structure or organisational principle, replete with quotations from biblical, Jewish, Greek 'gnostic' and Christian works of all genres. This thesis seeks to read this complex and erudite text in conversation with what has been termed the ‘Second Sophistic’, the efflorescence of elite Greek literature under the Roman empire. We will examine the the text as a performance of authorial persona, competing in the agonistic marketplace of Greek paideia. Clement presents himself as a philosophical teacher in a diadoche from the apostles, arrogating to himself a kind of apostolic authority which appeals to both philosophical notions of intellectual credibility and Christian notions of the authentic handing down of tradition. We will also examine how the work engages key thematic concerns of the period, particularly discourses of intellectual eclecticism and ethnicity, challenging both Greek and Roman forms of hegemony to create a space for Christian identity. Lastly, this thesis will critically examine the Stromateis' intertextual relationship with the Homeric epics; the Iliad and the Odyssey are used as a testing ground for Christian self-positioning in relation to Greek culture as a whole. As we trace this variable relationship, we will also see the cross-fertilisation of reading strategies between Homer and the bible; these developing complex allegorical methods not only presage the rise of Neoplatonism, but also lay the foundations for changes in cultural authority which accompany the Christianisaton of the Roman empire in the centuries after Clement.